2019
DOI: 10.1534/g3.119.400130
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency CRISPR/Cas9-Mediated Gene Editing in Honeybee (Apis mellifera) Embryos

Abstract: The honeybee ( Apis mellifera ) is an important insect pollinator of wild flowers and crops, playing critical roles in the global ecosystem. Additionally, the honeybee serves as an ideal social insect model. Therefore, functional studies on honeybee genes are of great interest. However, until now, effective gene manipulation methods have not been available in honeybees. Here, we reported an improved CRISPR/Cas9 gene-editing method by microinjecting sgRNA and Cas9 protein into the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Finally, we note that should a gene drive for these wasps be desired, significant challenges still lie ahead in the production of a transgenic wasp line. The efficient production of CRISPR-Cas9 modified hymenopteran insects including honey bees ( Apis mellifera ) 56 and ants 57 offers avenues for this work.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we note that should a gene drive for these wasps be desired, significant challenges still lie ahead in the production of a transgenic wasp line. The efficient production of CRISPR-Cas9 modified hymenopteran insects including honey bees ( Apis mellifera ) 56 and ants 57 offers avenues for this work.…”
Section: Resultsmentioning
confidence: 99%
“…With CRISPR-Cas-assisted accurate cleavage in target DNA sequences and thus introducing double-stranded DNA (dsDNA) breaks (DSBs), the genome engineering efficiency can be greatly improved. Up to date, both the type II Cas9 system and type V Cas12a system have been widely applied in genome editing in a large number of species ( Cong et al, 2013 ; Jiang et al, 2014 , 2015 ; Cobb et al, 2015 ; Huang et al, 2015 ; Matsu-Ura et al, 2015 ; Low et al, 2016 ; Jia et al, 2017 ; Harrison and Hart, 2018 ; Hu et al, 2019 ). Compared to Cas9, Cas12a has several distinct features, including the preference of T-rich PAM sequences and the staggered cleavage pattern against target dsDNA ( Zetsche et al, 2015 ; Yamano et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kohno et al (2016) reported the first application of CRISPR/Cas9 in the honey bee with the production of mutant drones [63]. Currently, there are several reports of the application of CRISPR/Cas9 in the honey bee, and two procedures for analyzing gene function have been proposed [63,64,65,66].…”
Section: Genetic Methods Applied To the Honey Beementioning
confidence: 99%
“…That report was the first functional analysis using mutant honey bee workers. Xiao et al (2019) also reported highly efficient genome editing in the honey bee using similar methods [66]. Although they only analyzed embryos before they had hatched, they demonstrated that this method is effective for analyzing gene function.…”
Section: Genetic Methods Applied To the Honey Beementioning
confidence: 99%